The relationship between working environment and job satisfaction among employees at Ibu Pejabat Polis Daerah Kota Samarahan, Sarawak / Hazirah Afifah Mustafa - Mustafa, Hazirah Afifah (2018)
The purpose of this paper is to examine the relationship between working environment and job satisfaction among public sector employees at Ibu Pejabat Polis Daerah Kota Samarahan, Sarawak. It can be hypothesized that there are a positive relationship between working environment and job satisfaction. Working environment plays an important role in the job satisfaction of an employee. Results were analysed with normality analysis, descriptive analysis, reliability analysis and correlation analysis. The study found the job satisfaction has strong, positive and significant relationship between working environment and job satisfaction. This paper also present the recommendation made for future researcher and an organization.